Evolving longer for a mate: A new scorpionfly (Mecoptera: Panorpoidea: Panorpidae) with exaggeratedly elongated male abdominal segments - Wang, Ji-Shen (Zootaxa, 2023)
Male scorpionflies often evolve exaggeratedly elongated abdominal segments (EEAS) that are used as a sexual display to the females, and a combat weapon in intra-sexual disputes. EEAS have independently evolved several times since the Jurassic till the present day in at least eight genera and four families. In this paper, Neopanorpa exaggerata sp. n. with EEAS is described from Yunnan Province, China. Through comparisons among extinct and extant species, our current knowledge is summarized for the evolution, copulatory mechanism, and biogeography of the scorpionflies with EEAS. Also discussed are the trade-offs between the benefits of “looking sexy” and the negative impacts associated with a long abdomen. Additionally, further clarification is provided on the multiple origins of EEAS in Panorpoidea.